Resilience processes, engagement and emotional competencies, in professionals attending elder people in violence situations in Saltillo, Coahuila and Monterrey, Nuevo León, Mexico = Procesos de resiliencia, engagement y competencias emocionales en profesionales de atención a población adulta mayor en situaciones de violencia en Saltillo, Coahuila y Monterrey, Nuevo León México - Castro Saucedo, Laura Karina
In recent years, an increasing number of studies have investigated resilience, which is considered a phylogenetic process developed to increase survival (Stein, 2009; Aparecida dos Santos & Nunes Moreira, 2014). Resilience is a construct that has been the topic of many studies. The objective of this investigation is to identify the relationship between the five dimensions of resilience in professionals who tend to elderly people, labor engagement and the emotional competencies. Several linear regression models were used to investigate the levels of prediction between the independent and dependent variables. The main results show relationships among resilience and its different dimensions, engagement (β = .207; p = .005) and emotional competencies (β =.710; p =.001) including four of its five dimensions on the analysis (R2= .724, F = 108.63, gl = 2, p= .001).